The Blinding Lights of (Post)feminist Empowerment in Joyce Carol Oates’s "Night, Neon” - Stéphanie Maerten (Bearing Witness: Joyce Carol Oates Studies)
Juliana, the protagonist of Joyce Carol Oates’s 2018 novella “Night, Neon,” is portrayed as a confident, empowered young woman who appears to embody the postfeminist ideal of “having it all”—autonomy, agency, and adherence to traditional feminine norms like marriage and motherhood. However, as the story unfolds, it becomes evident that Juliana’s sense of empowerment is largely performative, concealing deep-seated vulnerabilities and unresolved traumas. Through a series of flashbacks revealing Juliana’s troubled past, Oates critiques the postfeminist tendency to reinterpret traumatic experiences as tools for self-empowerment and resilience, suggesting that such a framework may obscure the systemic and pervasive nature of violence against women. By drawing parallels between Juliana and earlier Oates heroines, this article argues that Oates challenges the postfeminist narrative, exposing its limitations and the enduring influence of entrenched gender dynamics. Ultimately, the story underscores the complexities of contemporary womanhood, and the dangers of embracing an illusion of empowerment that fails to address underlying issues of gender inequality.